Chemokine/cytokine-releasing biomaterials induce in situ tertiary lymphoid–like structures and enhance antitumor immunity - Rana Falahat; James J. Mulé (Proceedings of the National Academy of Sciences, 2025)
Despite the growing recognition of tertiary lymphoid structures (TLSs) as valuable prognostic markers in certain cancer types, detailed studies on their development and therapeutic function remain limited. This is partially due to the lack of appropriate preclinical animal models. In this study and based on our earlier work [D. Coppola et al., Am. J. Pathol. 179 , 37–45 (2011); J. L. Messina et al., Sci. Rep. 2 , 765 (2012)], we hypothesized that encapsulating lymphoid chemokines and cytokines in controlled-release biomaterials would allow for their sustained delivery to the local tissue microenvironment, promote immune T-cell and B-cell accumulation, and lead to the in situ formation of TLS-like structures. To test this hypothesis, we encapsulated CCL19, CCL21, CXCL13, and lymphotoxin-α1β2 in lipid-coated microparticles (MPs) and embedded them in a biodegradable thermosensitive hydrogel designed to gel rapidly and release encapsulated payloads at injection sites over several days. In mice, subcutaneous injections of chemokine/cytokine-releasing MPs in hydrogel led to a substantial increase in CD45 + immune cell accumulation within newly developed structures surrounding the residual hydrogel after 3 wk. This influx was accompanied by a marked increase in the numbers of CD19 + B cells and CD3 + T cells. Using a mouse model of melanoma, we further show these induced structures can suppress tumor growth by promoting tumor antigen-specific T-cell responses. These findings indicate that chemokine/cytokine-releasing MPs in hydrogel can induce lymphoid structures resembling TLSs, highlighting their potential both as preclinical models for elucidating mechanisms regulating TLS formation and as platforms for therapeutic interventions against tumors.